Effect of copper foam thickness on pool boiling heat transfer of HFE-7100 - Manetti, Leonardo Lachi [UNESP] (2020)
Pool boiling is a low-cost technique for cooling electronic devices; HFE-7100 is a dielectric fluid with advantageous properties for such application but its high wettability can cause temperature overshoot in the system. Hence, the use of porous heating surfaces improves the heat transfer performance, eliminating the temperature overshoot due to their interconnected porous, which increase the wetted area and active nucleation site density. This work addressed pool boiling tests by using HFE-7100 and copper foams with three different thicknesses: 3 mm, 2 mm, and 1 mm in order to study the vapor bubble dynamics into the foam cell and find out an optimum thickness to enhance the boiling heat transfer. The results show that high thickness, 2 mm and 3 mm, has the best performance at low heat fluxes while the lowest thickness has the best performance at high heat fluxes. At heat fluxes lower than 50 kW/m², the higher surface wetted area increases the natural convection zone even though the latent heat also plays an important role. At higher heat fluxes, mainly after 200 kW/m², the vapor bubbles are trapped at the foam structure leading to an unstable boiling pattern and prevent the liquid from rewetting the surface. Therefore, the lowest foam thickness reduces the vapor trapping into the cell; additionally, the capillary-wicking ability increases and it also improves the HTC and the dryout heat flux due to the prevention of hotspots within the foam surface.